Evaluation of Cottonseed Meal as an Alternative to Fish Meal in Diet for Juvenile Asian Red-Tailed Catfish Hemibagrus wyckioides. (6th January 2023) - Li, Biwei; Su, Linhai; Sun, Yan; Huang, Han; Deng, Junming; Cao, Zhiyong
Abstract : A 10-week trial was performed to investigate the effects of replacing fishmeal with cottonseed meal (CSM) on the growth rate, protein metabolism, and antioxidant response of Asian red-tailed catfish Hemibagrus wyckioides . Five isonitrogenous and isocaloric diets (C0, C8.5, C17.2, C25.7, and C34.4) were prepared to contain 0%, 8.5%, 17.2%, 25.7%, and 34.4% CSM replacing fishmeal, respectively. The weight gain, daily growth coefficient, pepsin, and intestinal amylase activities initially increased and then decreased with the raising dietary CSM levels; the highest values were observed in the C17.2 group (P < 0.05 ). However, feed cost exhibited the opposite trend. With the increasing dietary CSM levels, the protein efficiency ratio and intestinal trypsin activity decreased but feed conversion rate increased gradually; while no differences were observed among the C0, C8.5, and C17.2 groups (P > 0.05 ). Dietary CSM inclusion regardless of levels increased the plasma growth hormone level as well as hepatic aspartate aminotransferase (AST) and γ -glutamyl transpeptidase activities but decreased the plasma glutamate dehydrogenase and AST activities (P < 0.05 ). With the increasing dietary CSM levels, the plasma alkaline phosphatase (AKP) and hepatic superoxide dismutase activities decreased but malondialdehyde content increased gradually, while no differences were observed among the C0, C8.5, and C17.2 groups (P > 0.05 ). The plasma immunoglobulin M content and hepatic glutathione reductase activity initially increased but then decreased with the raising dietary CSM levels; the highest values were found in the C17.2 group. These results indicated that dietary CSM inclusion level up to 17.2% improved the growth rate, feed cost, digestive enzyme activity, and protein metabolism without compromising antioxidant capacity of H. wyckioide, whereas these parameters were depressed by further inclusion of CSM. CSM is a potentially cost-effective alternative plant protein source in diet of H. wyckioide .